Patterns of Fine Needle Aspiration Cytology Diagnosed Thyroid Nodules Among Clinically Suspected Patients in Northeast Ethiopia - Ebrahim H; Tilahun M; Fiseha T; Debash H; Bisetegn H; Alemayehu E; Fiseha M; Ebrahim E; Shibabaw A; Seid A; Getacher Feleke D; Mohammed O (Dove Medical Press, 2023)
Hussen Ebrahim,1 Mihret Tilahun,1 Temesgen Fiseha,1 Habtu Debash,1 Habtye Bisetegn,1 Ermiyas Alemayehu,1 Mesfin Fiseha,1 Endris Ebrahim,1 Agumas Shibabaw,1 Abdurahaman Seid,1 Daniel Getacher Feleke,2 Ousman Mohammed1 1Department of Medical Laboratory Sciences, College of Medicine and Health Sciences, Wollo University, Dessie, Ethiopia; 2Department of Microbiology, Immunology, and Parasitology, College of Health Sciences, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Hussen Ebrahim, Po.Box:1145, Tel +251921332772, Email husshosam@gmail.comBackground: Thyroid nodules are the most common thyroid disease and its incidence has been rising throughout the world. Thus, this study aimed to assess the patterns of fine needle aspiration cytology-diagnosed thyroid nodules among clinically suspected patients.Methods: A prospective cross-sectional study was conducted from April 2021 to March 2022 using 424 study participants who were referred to undergo fine needle aspiration cytology examination and were consecutively included. Moreover, two FNAC smears were prepared and stained using Wright and Giemsa staining solutions and then examined by an experienced licensed pathologist. Multivariate logistic regression was used to determine the association of socio-demographic and clinical variables with nodules. P-value < 0.05 was considered to be statistically significant.Results: The overall magnitude of benign and malignant nodules was 60.4% and 16.5% respectively. Moreover, the magnitude of atypical of undetermined significance or follicular lesion of undetermined significance (AUS/FLUS) and follicular neoplasm or suspicious of follicular neoplasm (FN/SFN) was 3.54% and 1.42% respectively. The magnitude of malignant thyroid nodules was 5.9% for malignant secondary adenocarcinoma, 3.5% for papillary thyroid carcinoma, 2.6% for Non-Hodgkin lymphoma, 2.4% for medullary thyroid carcinoma, 1.4% of an undifferentiated malignant thyroid tumor and 0.7% of Hodgkin lymphoma respectively. Multivariate logistic regression showed that age categories between 0 and 15 years and between 16 and 30 years, and nodule size > 2.5cm were significantly associated with malignant thyroid nodules.Conclusion: The magnitude of benign and malignant tumors was 60.4% and 16.5% respectively. Being younger and having nodule size > 2.5cm were significantly associated with malignant thyroid nodules. Therefore, fine needle aspiration cytology examination has a crucial role in the diagnosis and management of benign and malignant thyroid nodules.Keywords: benign, cytology, fine needle aspiration, malignant, thyroid tumors, thyroid gland, thyroid nodules, ultrasound, Ethiopia